The Effect Of Product Quality And Price On Coal Purchase Interest Through Sales Based On Non-Kai Logistics At Pt Bukit Asam, Tbk - Rendra Haryadi; Marlina Widiyanti; Muchsin Saggaff Shihab; Ahmad Maulana (Journal Of Social Science (JoSS), 2024)
This study aims to analyze the effect of product quality and price on coal purchase interest through non-KAI-based logistics sales at PT Bukit Asam, Tbk. The background of this research is driven by the challenges faced by the company in increasing purchase interest through more flexible distribution strategies and reducing reliance on railway transportation. The research method used is quantitative, with data collected through surveys of 150 respondents, consisting of customers and brokers. Data analysis was conducted using multiple linear regression. The results show that product quality and price positively and significantly impact coal purchase interest. High product quality has been proven to enhance customer satisfaction, while competitive pricing is crucial in attracting consumer interest. In conclusion, PT Bukit Asam, Tbk, should continue to improve service quality and offer more competitive prices to expand its market and increase sales through the non-KAI logistics system.